"The fire below": Towards a new study of literatures and cultures (in English?) A letter from a literary scholar in a South African university in transition. (February 2016) - Collis-Buthelezi, Victoria J
This letter was first read as a seminar paper in the Institute for the Humanities in Africa at the University of Cape Town in which I offer a series of provocations about what our current moment asks of us. It is concerned with the future of literary and cultural studies (in English) at that university and in South Africa in the wake of the RhodesMustFall movement. I look at the formation of English literature in colonial India and the rise of black studies in the US as I think through the emerging cry for decolonization of curricula in higher education in South Africa. I contemplate literary and cultural studies as modes of reading and making consent.